The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5978/islsm.16-or-01
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment with a fractional CO2 laser enhances shear bond strength of resin cement to zirconia

Abstract: Aims:The present study investigated the effect of different surface treatments on shear bond strength (SBS) of resin cement to zirconia. Materials and methods: Ninety zirconia blocks were prepared and divided into 6 groups of 15 by treatment. Group 1 served as the control group, whereas groups 2 and 3 were treated with air abrasion and a universal primer (Monobond plus), respectively. The remaining zirconia copings were treated with a fractional CO2 laser for 10 seconds using 10 W/10 mJ (group 4), 10 w/14 mJ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 34 publications
(13 reference statements)
2
36
0
1
Order By: Relevance
“…It also increases the surface area and surface energy for the adhesion of resin cements and promotes micromechanical retention 44) . However, bonding to Y-TZP has always been a challenging issue, as the material is acid-resistant due to its polycrystalline structure 29,35,45) . To achieve adequate bond strength between Y-TZP and resin cement, airborne particle abrasion is recommended 36,46) .…”
Section: Discussionmentioning
confidence: 99%
“…It also increases the surface area and surface energy for the adhesion of resin cements and promotes micromechanical retention 44) . However, bonding to Y-TZP has always been a challenging issue, as the material is acid-resistant due to its polycrystalline structure 29,35,45) . To achieve adequate bond strength between Y-TZP and resin cement, airborne particle abrasion is recommended 36,46) .…”
Section: Discussionmentioning
confidence: 99%
“…This result can be attributed to the performance of CO2 laser irradiation in roughening ceramic surface through thermo-mechanical ablation, which increases micro-mechanical retention. This enhances the bond strength at the zirconia/cement interface 26,39) .…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that CO2 laser could provide the highest bond strength in In-Ceram Spinel group while in In-Ceram Alumina no significant difference was found among various surface treatments. The laser settings applied in this study were selected according to the results of previous studies 12,25 and the results of our pilot study to find the minimum laser parameters that can etch the porcelain surface. Some studies reported increased surface roughness after the use of different lasers for surface conditioning of ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of power and energy were 20 W/10 mJ and 15 W/ 20 mJ in groups 3 and 4, respectively. These parameters were taken from previous studies, 12,25 and the results of our pilot study (data have not been presented) to find the parameters that etch the feldspathic porcelain without creating visible thermal damage. The surfaces of the specimens in group 5 were first irradiated with the fractional CO2 laser under the same conditions as described in group 4 (15 W/20 mJ) and then treated with 9.6% HF acid for 2 minutes, similar to the control group.…”
Section: Methodsmentioning
confidence: 99%